1996
DOI: 10.1177/014572179602200204
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Adolescents With Diabetes

Abstract: This study investigated the physical activity and beliefs about exercise of 30 adolescents with diabetes. The Seven-Day Physical Activity Recall was used to determine the physical activity for two different recall periods that were 2-weeks apart. Forty percent of the youths engaged in 30 minutes of moderate activity 5 times per week while only 10% engaged in 20 minutes of vigorous activity 3 times per week. Forty-seven percent of the teens consistently achieved or surpassed the time equivalent of activity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
1
24
1
Order By: Relevance
“…27 Our diabetic children accumulated 35-45 minutes/day of moderate activity and 20-25 minutes/day of aerobic vigorous activity. Contrary to other studies, [30][31][32][33] they compare favourably with their healthy peers. 10 As the healthy subjects received no educational programme with promotion of physical activity, it suggests that our educational programme for diabetic patients may influence their physical activity behaviour.…”
Section: Discussioncontrasting
confidence: 95%
“…27 Our diabetic children accumulated 35-45 minutes/day of moderate activity and 20-25 minutes/day of aerobic vigorous activity. Contrary to other studies, [30][31][32][33] they compare favourably with their healthy peers. 10 As the healthy subjects received no educational programme with promotion of physical activity, it suggests that our educational programme for diabetic patients may influence their physical activity behaviour.…”
Section: Discussioncontrasting
confidence: 95%
“…A recent study using accelerometers assessed physical activity in 26 adolescent girls with Type 1 diabetes and found no association between these measurements and HbA 1c (Sarnblad et al, 2005). This concurred with the findings of previous cross-sectional research which investigated self-reported physical activity and metabolic control in children with Type 1 diabetes (Bennett Johnson et al, 1990;Hanson et al, 1996;Loman & Galgani, 1996).…”
Section: Introductionsupporting
confidence: 71%
“…There have been larger studies which have assessed the relationship between HbA 1c and self reported physical activity (Bennett Johnson et al, 1990;Hanson et al, 1996;Loman & Galgani, 1996), it is agreed though that objective monitoring is a more valid method of assessing physical activity particularly in children (Armstrong & Welsman, 1997). The only other study which provided an objective measurement of physical activity of children with Type 1 diabetes included 26 participants with Type 1 diabetes (Sarnblad et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall (Sallis, Buono, Roby, Micale, & Nelson, 1993); METS = metabolic equivalents; Exercise Beliefs = Exercise Belief Instrument for Adolescents (Loman & Galgani, 1996 NOTE: Hz = Hertz; PAR = Seven-Day Physical Activity Recall (Sallis, Buono, Roby, Micale, & Nelson, 1993); Exercise Beliefs = Exercise Belief Instrument for Adolescents (Loman & Galgani, 1996); DM = diabetes mellitus; HbA lc = glycosylated hemoglobin; SDNN = standard deviation of all R-R intervals; SDANN = standard deviation of all the means of R-R intervals for each 5-minute block; SD = mean of the standard deviation of the R-R intervals of each 5-min block; pNN50 = % of adjacent R-R intervals with ≥50 ms difference; rMSSD = square root of the mean of the sum of squares of differences between adjacent R-R intervals.…”
Section: Discussionmentioning
confidence: 99%